HUBUNGAN KADAR HEMOGLOBIN PADA IBU HAMIL TM III DENGAN PERTUMBUHAN JANIN (TINGGI FUNDUS UTERI) - Sumy Dwi Antono, Sumy Dwi Antono; Siti Asiyah, Siti Asiyah (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2013)
Low Birth weight is one of the problems that exist in Indonesia,in 2003 68% of neonatal deaths due to low birth weight, low birth weight is due to occurrence of impaired fetal growth. The cause of impired fetal growth is due to hypoxia of the fetus in the womb caused by low levels of hemoglobin during the third semester of pregnancy. The purpose of this study was to know the relation of hemoglobin levels in the third pregnant mother with fetal growth (fundus high). This study is correlative study with cross sectional design. The subject of this study is part of the pregnant women in Puskesmas Mricanâs working area, there are 33 pregnant womensfrom these studies found 20 respondens with Hb levels â¥11gr%, 18 of them have normal fetal growth,and then respondents with Hb levels 9-10,9gr% there were 11 respondents,there are 6 respondents which impaired fetal growth and 3 respondent normal fetal growth, 2 respondents with big baby. It also found respondents with Hb level 7-8,9gr% there are 2 respondent where both impired fetal growth. Data were processed using Spearman rank correlation test, with standard error 0.05 t count =7,523 and then t table: 2,042, so t count > t table. It means that There is a relation between hemoglobin levels in third semester pregnant mother with fetal growth (Fundus High).Â Keywords: Hemoglobin Levels in the third semester of pregnant mother, fetal growth (fundus high)Â